KONTRIBUSI MATA PELAJARAN PKKJ TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI TEKNIK OTOMOTIF DI SMK NEGERI 2 PAYAKUMBUH - Wagino Wagino; Altifani Dasla; Hasan Maksum; Donny Fernandez (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The scarcity of employment is what spurred this investigation. the high unemployment rate, the limited interest in business among many graduates of technical schools. The purpose of the study was to determine how much the creative product and entrepreneurship majors (MPPKKJ) classes at SMK Negeri 2 Payakumbuh affected students in Class XI Automotive Engineering's motivation in starting their own business. This study is an example of a quantitative correlational study. 54 pupils were chosen at random from a population of 105 students. Microsoft Excel 2010 was used to input the data, and SPSS version 16 was utilised to analyse it. 88.94% of the study data for variable (X) fell into the good category, whereas 90.54% of the data for variable (Y) fell into the very excellent category. Testing the correlation theory produced results in the reasonably high category of Rcount 0.652 > Rtable 0.263. According to the findings of the t-test, MPPKKJ and interest in entrepreneurship are positively correlated (Tcount 6.2 > Ttable 1.674). The results showed that the MPPKKJ variable contributed 41.4% to interest in entrepreneurship, whereas 58.6% was impacted by other variables. Keywords: Creative Product Subject and Entrepreneurship Department, Interest in Entrepreneurship